RW-Through: A Data Replication Protocol Suitable for GeoDistributed and Read-Intensive Workloads - Barretto, Wagner Rezende Muniz; B. Kochem Vendramin, Ana Cristina; Fonseca, Mauro (Anais do Workshop em Clouds e Aplicações (WCGA), 2019)
In large-scale modern applications, users consume much more datathan they create. To guarantee that data storage systems appropriately han-dle read-intensive workloads, application designers have been adopting datareplication and caching techniques. These techniques face many challenges re-garding data consistency, specially in faulty network conditions such as wide-area networks. In this work we use recent distributed consistency frameworksto identify the consistency models of the main solutions for read-intensive work-loads used today in the industry. Additionally, we present RW-Through, a newdata replication protocol suited for large-scale read-intensive workloads. Ournew protocol provides stronger consistency guarantees than current solutionsand is designed to tolerate unreliable network conditions, making it suitable forgeo-distributed deployments.